2005
DOI: 10.1007/s11232-005-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

Center-of-mass tomography and probability representation of quantum states for tunneling

Abstract: We develop a representation of quantum states in which the states are described by fair probability distribution functions instead of wave functions and density operators. We present a one-random-variable tomography map of density operators onto the probability distributions, the random variable being analogous to the center-of-mass coordinate considered in reference frames rotated and scaled in the phase space. We derive the evolution equation for the quantum state probability distribution and analyze the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Starting from pioneer work in the field [4], parameterization through the Euler angles was suggested as a physically natural alternative to (9). The use of the Euler angles is one of the ways to represent the rotation of R 3 .…”
Section: Spin Tomogram As Function Of the Euler Anglesmentioning
confidence: 99%
“…Starting from pioneer work in the field [4], parameterization through the Euler angles was suggested as a physically natural alternative to (9). The use of the Euler angles is one of the ways to represent the rotation of R 3 .…”
Section: Spin Tomogram As Function Of the Euler Anglesmentioning
confidence: 99%
“…, X N ) T , H n denotes the Hermite polynomial and we put m = Ω = 1 for the mass as well as the frequency. In the case, taking into account that we do not put = 1 like it was done in [2,3]) we get…”
Section: Excited States Of a Quantum Oscillatormentioning
confidence: 99%
“…In [1] we studied the center-of-mass tomogram [2,3] in the limiting case of many degrees of freedom N → +∞. It was shown that the final distribution tends to Gaussian if the state of the initial system is a product of excited states of a quantum oscillator and some additional conditions are satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another line of studies, simulation of quantum systems have been performed using tomography. For example, tomograms were used for simulation of tunneling [25][26][27] and multimode quantum states [28]. Attempts have also been made to understand the tomogram via path integrals [29,30].…”
Section: Introductionmentioning
confidence: 99%